The value of off-pump coronary artery bypass grafting in the surgery for combined valvular and coronary heart disease - Qin, Haokai; Si, Pengrui; Hua, Kun; Yang, Xiubin (Frontiers in Medicine, 2024)
Background Combined valve and coronary surgery is a commonly performed surgical technique for treating coexisting valvular and coronary artery disease. This study aims to investigate the effect of reducing the duration of cardiopulmonary bypass by utilizing the off-pump coronary artery bypass grafting (OPCABG) technique on the short-term prognosis of patients. Methods In this retrospective cohort study, 884 patients were divided into groups undergoing OPCABG or on-pump CABG combined with valve surgery based on the CABG technique. We evaluated the relationship between the surgical technique and operative mortality, postoperative atrial fibrillation (POAF), stroke, acute kidney failure (AKI), and perioperative myocardial infarction. Propensity score matching and inverse probability weighting (IPTW) were employed to mitigate differences in baseline characteristics between the two groups. Results The incidence of POAF and AKI were lower in the OPCABG group after IPTW (POAF: 29.5% vs. 39.5%, p = 0.016; AKI: 14.5% vs. 21.2%, p = 0.047). OPCABG technique was independently associated with the POAF (adjusted OR: 0.63, 95% CI: 0.44–0.91, p = 0.014) and AKI (adjusted OR: 0.63, 95% CI: 0.39–0.98, p = 0.049). These results remained even following PSM and IPTW analyses. Conclusion The OPCABG technique is associated with reduced occurrences of POAF and AKI in patients undergoing valve and concomitant coronary surgery and can be safely used.